Entrepreneurial Mindset & Methods - Inud Danis Ikhwan Meranti (Journal of Economic Perspectives and Business Innovation, 2024)
AbstractEntrepreneurial mindset and methods play a critical role in shaping innovation, opportunity recognition, and sustainable business growth in an increasingly competitive global economy. This study explores the conceptual foundations of the entrepreneurial mindset and examines practical methods that enable entrepreneurs to adapt to uncertainty, manage risk, and create value. Using a qualitative literature-based approach, the research synthesizes key theories of entrepreneurship, behavioral traits, and strategic decision-making frameworks. The findings indicate that a strong entrepreneurial mindset is characterized by resilience, creativity, proactive learning, and opportunity-driven thinking. Furthermore, structured entrepreneurial methods—such as lean experimentation, customer-centered innovation, and iterative problem solving—significantly enhance venture performance and long-term sustainability. The study concludes that integrating mindset development with practical entrepreneurial tools is essential for fostering adaptive and competitive entrepreneurs in modern markets. Keywords: entrepreneurial mindset, innovation, opportunity recognition, business strategy, entrepreneurship methods